Genotypic associations of the hepatic secretion of VLDL apolipoprotein B-100 in obesity - G.F. Watts; F.M. Riches; S.E. Humphries; P.J. Talmud; F.M. van Bockxmeer (Journal of Lipid Research, 2000)
Abstract: We examined the effect of genetic polymorphisms of proteins regulating intrahepatic processing of apolipoprotein B-100 (apoB) and the supply of neutral lipids to the liver on the hepatic secretion of very low density lipoprotein (VLDL) apoB in obesity. Hepatic secretion of very low density apolipoprotein B-100 (VLDL apoB) was measured using an infusion of [1-13C]leucine in 29 obese men. Isotopic enrichment and turnover of VLDL apoB was determined using gas chromatography–mass spectrometry and multi-compartmental modelling, respectively. Visceral fat was measured by magnetic resonance imaging. Genotypes for the apoB signal peptide (SP27/SP24 alleles), microsomal triglyceride transfer protein promoter (MTP, −493 G/T alleles), apoE (E2, E3, E4 alleles), hepatic lipase promoter (−514 C/T alleles), and cholesteryl ester transfer protein (CETP, Taq1B B1/B2 alleles) were determined using polymerase chain reaction. Statistically significant associations were found between hepatic secretion of apoB and allelic combinations of i) apoB SP with apoE (P = 0.02), hepatic lipase (P = 0.02), and CETP (P = 0.006) genes, ii) MTP promoter with CETP genes (P = 0.03); the association with apoBSP/MTP promoter allelic combinations just failed to reach significance (P = 0.06), however. The CETP/apoBSP allelic combination was the most significant predictor of apoB secretion, and this was independent of visceral fat, plasma lathosterol and insulin levels, and dietary fat. SP24 carriers who were homozygous for CETP B1 had 60% lower apoB secretion than B2 heterozygotes who were non-carriers of SP24 (10.5 ± 1.74 mg/kg fat free mass/day, n = 7 vs. 26.1 ± 3.16, n = 22). The data suggest that variation in both the apoB and CETP genes may be a major genetic determinant of the hepatic secretion of apoB in men with visceral obesity. —Watts, G. F., F. M. Riches, S. E. Humphries, P. J. Talmud, and F. M. Bockxmeer. Genotypic associations of the hepatic secretion of VLDL apolipoprotein B-100 in obesity. J. Lipid Res. 2000. 41: 481–488.